Atlantic meridional heat transports computed from balancing Earth's energy locally. Issue 4 (18th February 2017) - Trenberth, Kevin E.; Fasullo, John T.
Abstract: The Atlantic Meridional Overturning Circulation plays a major role in moving heat and carbon around in the ocean. A new estimate of ocean heat transports for 2000 through 2013 throughout the Atlantic is derived. Top‐of‐atmosphere radiation is combined with atmospheric reanalyses to estimate surface heat fluxes and combined with vertically integrated ocean heat content to estimate ocean heat transport divergence as a residual. Atlantic peak northward ocean heat transports average 1.18 ± 0.13 PW (1 sigma) at 15°N but vary considerably in latitude and time. Results agree well with observational estimates at 26.5°N from the RAPID array, but for 2004–2013 the meridional heat transport is 1.00 ± 0.11 PW versus 1.23 ± 0.11 PW for RAPID. In addition, these results have no hint of a trend, unlike the RAPID results. Strong westerlies north of a meridian drive ocean currents and an ocean heat loss into the atmosphere that is exacerbated by a decrease in ocean heat transport northward. Key Points: Energy budget indirect estimates of ocean heat transports for 2000‐2013 are much improved Time series of the AMOC meridional heat transports throughout the Atlantic are computed for 2000‐2013 At 26.5°N results complement measurements from the RAPID array but feature less trend and an offset